Faktor Risiko yang Berpengaruh terhadap Terjadinya Hipertensi pada Penderita Diabetes Melitus Tipe II di Wilayah Puskesmas Kabupaten Pati - Gracilaria Puspa Sari; Shofa Chasani; Tjokorda Gde Dalem Pemayun; Suharyo Hadisaputro; Heri Nugroho (Jurnal Epidemiologi Kesehatan Komunitas, 2017)
Background: The prevalence of hypertension in type 2 diabetic patients is 1,5-3 times higher than it is in nondiabetic individuals This chronic condition accelerates macrovascular complications. Research about risk factors of hypertension in type 2 diabetic patients is still rare because its causes multifactorial. The objectives of this research is to explain the risk factors affecting hypertension in type 2 diabetic patients.Methods: An observational studies with case-control study design in Primary Healthcare Centers patients in Pati District. Patients with hypertension in type 2 diabetes are the case, while the type 2 diabetes patients without hypertension are the control. There were 57 cases and 57 controls included. Data were obtained from medical records and qualitative interviews. Chi-square test in bivariate and multiple logistic regression in multivariate analysis.Results: Factors that influence hypertension in type 2 diabetic patients were physical activity (OR=6,4; 95% CI: 2,18 - 18,77; p=0,001), diabetes duration ≥ 5 years (OR=5,4; 95% CI: 1,97 - 14,704; p=0,001), and medication adherence (OR=3,6; 95% CI: 1,32 - 9,83; p=0,012). Other risk factors i.e age ≥45 years, male, diet compliance, history of hypertension, smoking, salt consumption, coffee consumption, and sleep duration were not significantly influenced.Conclusion: In this study, physical activity, diabetes duration, and DM medication adherence are risk factors that influence of hypertension in type 2 diabetic patients.